2009
DOI: 10.1007/s00421-009-1046-1
|View full text |Cite
|
Sign up to set email alerts
|

Thirteen days of “live high–train low” does not affect prooxidant/antioxidant balance in elite swimmers

Abstract: We investigated the impact of 13 days of "living high-training low" (LHTL) on the antioxidant/prooxidant balance in elite endurance swimmers. Eighteen elite swimmers from the French Swimming Federation were submitted to a 13-day endurance training and divided into two groups: one group trained at 1,200 m and lived in hypoxia (2,500-3,000 m simulated altitude) and the second group trained and lived at 1,200 m. The subjects performed an acute hypoxic test (10 min at 4,800 m) before and 1 day after the training p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 34 publications
2
29
1
Order By: Relevance
“…There was no effect for protein oxidation over shorter training periods at sea level, or at altitude using the PC assay in alpine skiers [126], and for 13 and 18 days at training (LLTL *1,200 m) using the AOPP assay in swimmers [124] and cross-country skiers [49]. In contrast, 13 and 18 days of training under LHTL conditions markedly increased biomarkers of protein oxidation in swimmers (38 %) and cross-country skiers (130 %) [49,124].…”
Section: Evidence For Arh Across a Training Cycle; Micro- Meso-and Mmentioning
confidence: 96%
See 4 more Smart Citations
“…There was no effect for protein oxidation over shorter training periods at sea level, or at altitude using the PC assay in alpine skiers [126], and for 13 and 18 days at training (LLTL *1,200 m) using the AOPP assay in swimmers [124] and cross-country skiers [49]. In contrast, 13 and 18 days of training under LHTL conditions markedly increased biomarkers of protein oxidation in swimmers (38 %) and cross-country skiers (130 %) [49,124].…”
Section: Evidence For Arh Across a Training Cycle; Micro- Meso-and Mmentioning
confidence: 96%
“…Six studies reported on biomarkers of total antioxidant status using trolox equivalent antioxidant capacity (TEAC), total antioxidant score (TAS), total peroxyl radical-trapping potential (TRAP) or ferric ion reducing antioxidant power (FRAP) assays, with no significant changes reported across training periods of 13-32 days in length at sea level or at low-level altitude in swimmers and middle-distance runners [49,123,124], between a pre-competitive phase and competitive phase in kayakers [129], or across an entire season in middle-distance runners [128]. However, a difference between seasons was observed for TAS [129].…”
Section: Evidence For Arh Across a Training Cycle; Micro- Meso-and Mmentioning
confidence: 99%
See 3 more Smart Citations